The king's ransom [large type] - Evanovich, Janet (Evanovich, Janet. Gabriela Rose novel, 2025)
"Gabriela Rose, recovery agent extraordinaire, can find just about anything. Too bad she can't seem to lose her ex-husband. And now he needs her help. His cousin Harley is in big trouble. As the president of a bank, he invested an astronomical amount of money in insuring some priceless artifacts at the urging of his board. But recently, these insured pieces started going missing. Gabriela travel around the world to find the missing works of art, keep Harvey out of jail, and save both his skin and his bank. Racing from New York to London to Cairo to Italy, Gabriela Rose is ingenious, charming, and ready for anything"--